P2.2 Ultrasound Speckle Tracking Helps Identify Vulnerable Carotid Plaques - Kaloshina, A.; Kerbikov, O.; Borskaya, E.; Voynov, S.; Krutova, T.; Averyanov, A. (Artery research, 2014)
Ultrasound Speckle Tracking, a novel technique used to assess regional mechanics of carotid wall and plaques. We hypothesized that vulnerable carotid plaques have higher intraplaque stretch which resulted in an increased difference in deformation between cap and core Methods Study population consisted of 39 patients with carotid atherosclerosis: 11 with acute atherothrombotic stroke and 28 asymptomatic patients with similar demographics and risk factors. For each plaque, maximum circumferential and longitudinal strain (Sc_Sl) and strain rate (SRc_SRl) were measured for cap, core and base. Plaque characteristics (echogenicity, degree of stenosis, surface, etc) were assessed. All plaques were divided into hyperechogenic(19) and echolucent(20) ones. Results Echolucent plaques underwent significantly higher deformations than hyperechogenic ones (Sc=4.06 vs 3.25, p<0.05) and they had significant difference in deformation between cap and core(p<0.05) whereas hyperechogenic plaques had no difference in deformation between segments (Sc=5.2_4.2_2.8 and 3.5_3.1_3.2 for cap, core and base of echolucent and hyperechogenic plaques, respectively). Moderate negative correlations were observed between echogenicity and deformations (r=−0.35_p<0.001 for cap_Sc). Symptomatic plaques had higher difference between cap and core Sl. Plaque internal deformation coefficient, Cpid=[(cap_Sl-core_Sl)/(core_Sl+base_Sl)]x100 was developed to quantify the relative deformation of different plaque segments. Based on ROC-analysis, plaques with Cpid>22.2 were associated with an ischemic event (sensitivity-55%, specificity-87%, AUC=0.693, p=0.0485). Logistic regression confirmed that Cpid>22.2 is an independent predictor of plaque vulnerability, OR=3.7, 95%_CI=0.8–22.8, controlling for age, gender, plaque length, degree of stenosis, echogenicity. Conclusions Mobility of echolucent plaques exceeds those of hyperechogenic ones. Difference in mobility between plaque segments may help identify plaque vulnerability.